Homecoming Parade 1952 ? 'There's Nothing Like a Dame' (1952)
Float (car) in 1952's homecoming parade. Text on side of car reads, 'There's nothing like a dame,' student wearing mop-wig sits in passenger seat, and another student positions himself on the hood of the car along with a Stop For Pedestrians sign.